An improved explicit time integration method for linear and nonlinear structural dynamics. (15th August 2018) - Kim, Wooram; Lee, Jin Ho
Highlights: It is a true self-starting explicit method for structural dynamics. It is applicable to linear and nonlinear problems in a consistent way. No iterative procedure is required within a time step. Controllable numerical dissipation is achieved. Nonlinear performance is enhanced compare with existing methods. Abstract: In this article, a new explicit time integration method is developed to analyze linear and nonlinear problems of structural dynamics. Like recently developed explicit time integration methods, the new explicit method can also control the amount of numerical dissipation in the high frequency range. The method is explicit in the presence of the damping matrix, if the mass matrix is diagonal. Due to the unconventional approximations of the displacement vector, the new method does not require evaluation of the initial acceleration vector and other acceleration vectors. Linear and nonlinear problems of structural dynamics can be tackled in a consistent manner, and iterative solution finding procedures are not required. Various illustrative problems are used to investigate improved performance of the new explicit method.